2022
DOI: 10.31703/grr.2022(vii-ii).16
|View full text |Cite
|
Sign up to set email alerts
|

Trainee's Motivation to Transfer has Moderating Effect on the Relationship of Trainees Learning and Trainee's Behaviour in Social Enterprises of Pakistan

Abstract: Trainees' learning from training is an important factor for behavior change of the trainees.The current study's aim is to investigate the relationship between trainees' learning and trainee behavior in social enterprises operating in Pakistan. The study further investigates the moderating influence of trainees' motivation to transfer in the relationship amid trainees' learning and trainees' behavior. The questionnaires adopted relevant to variables were distributed among skill certification training program tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The findings of Pudjiarti et al (2019) and Islam (2019) also support the discovery made relative to the influence assimilated training content has on motivation to transfer. Similarly, the revelation regarding assimilated training content and training transfer in this study is similar to those by Nafukho et al (2017), Ali et al (2022) and Dewayani and Ferdinand (2019). The influence of motivation to transfer on training transfer is in line with the studies of Arasanmi (2019), Bhatti et al (2013), Chiaburu et al (2010), Na-nan et al (2017), Na-nan and Sanamthong (2020), Salamon et al (2022a) and Salamon et al (2022b).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings of Pudjiarti et al (2019) and Islam (2019) also support the discovery made relative to the influence assimilated training content has on motivation to transfer. Similarly, the revelation regarding assimilated training content and training transfer in this study is similar to those by Nafukho et al (2017), Ali et al (2022) and Dewayani and Ferdinand (2019). The influence of motivation to transfer on training transfer is in line with the studies of Arasanmi (2019), Bhatti et al (2013), Chiaburu et al (2010), Na-nan et al (2017), Na-nan and Sanamthong (2020), Salamon et al (2022a) and Salamon et al (2022b).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, according toIslam (2019), low resistance to change learning culture is more likely to influence motivation to transfer. Again,Pudjiarti et al (2019) revealed that transformative learning and motivation to transfer are significantly related Ali et al (2022). found trainees' learning to be related to post-training behavior.…”
mentioning
confidence: 94%
See 1 more Smart Citation